Evaluation of the Abilities of Teachers and Students to Develop Emotional Intelligence in Preschool - somayeh ebneroomi; ali hosainikhah; majid aliasgari (پژوهش در نظام‌های آموزشی, 2020)
The purpose of this study was to identify the characteristics of teachers and students for the development of emotional intelligence in preschool. The research method was synthesis study. The statistical population of the research consisted of all documents, articles, scientific books, dissertations, scientific sources and scientific databases related to determining the required attributes of teachers and students for pre-school emotional education. 79 sources were selected using purposive sampling method. Data were analyzed in three ways: open coding, axial coding, and selective coding. The findings showed that the characteristics of preschool children for emotional intelligence development are: interaction with the environment, interactivity, affectivity of emotions, selection, gender recognition, perception of differences and similarities, emotionality, etc. The characteristics of coaches / teachers for emotional intelligence are: From: Emotional Expression, Planner and Concept Carrier, Questioning, Acting, Child Recognition, Artist, Process-Oriented, Child Play Recognition, etc ... In terms of subject matter, there are also integrated preschool courses based on these themes: content integration, Skill integration, Process integration, Learning environment integration, Tel Discern something, combined courses, combining and integrating role activity.